2007
DOI: 10.1007/s00442-007-0836-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial responses to nitrogen addition in three contrasting grassland ecosystems

Abstract: The effects of global N enrichment on soil processes in grassland ecosystems have received relatively little study. We assessed microbial community response to experimental increases in N availability by measuring extracellular enzyme activity (EEA) in soils from three grasslands with contrasting edaphic and climatic characteristics: a semiarid grassland at the Sevilleta National Wildlife Refuge, New Mexico, USA (SEV), and mesic grasslands at Konza Prairie, Kansas, USA (KNZ) and Ukulinga Research Farm, KwaZulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(98 citation statements)
references
References 69 publications
4
87
3
1
Order By: Relevance
“…Positive N addition effects on cellulose-degrading enzymes were also found in forest (Carreiro et al 2000;Saiya-Cork et al 2002;Allison et al 2008;Keeler et al 2009;Cusak et al 2011) and grassland studies (Ajwa et al 1999;Stursova et al 2006;Keeler et al 2009). Other studies, however, found that N addition can have variable effects on BG activity along a soil age gradient (Zeglin et al 2007) or that N fertilization does not have any significant effect on BG activity (Mineau et al 2014). Further research could address whether and how these variable effects of N fertilization on BG activity may depend on the spatial scale considered (i.e.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Positive N addition effects on cellulose-degrading enzymes were also found in forest (Carreiro et al 2000;Saiya-Cork et al 2002;Allison et al 2008;Keeler et al 2009;Cusak et al 2011) and grassland studies (Ajwa et al 1999;Stursova et al 2006;Keeler et al 2009). Other studies, however, found that N addition can have variable effects on BG activity along a soil age gradient (Zeglin et al 2007) or that N fertilization does not have any significant effect on BG activity (Mineau et al 2014). Further research could address whether and how these variable effects of N fertilization on BG activity may depend on the spatial scale considered (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies show that N inputs can have positive effects on total soil C stocks (Fornara et al 2013) and on the C content of both organic (Song et al 2014) and mineral soils (Liu and Greaver 2010;Fornara and Tilman 2012). Other studies show that N fertilization has no effect on the C content of bulk soils (Zeglin et al 2007) or on the C content of organic and mineral soils (Lu et al 2011). Such high soil C variability in response to N fertilization may depend on several environmental factors including differences in climate, soil and litter biochemical composition, management history, N addition rates and the time interval (years) to which soils have been exposed to chronic N additions; it may also depend on soil mineralogy and the reactivity of soil minerals (Sulman et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient chemistry of background water from the sites sampled here (Table 1) indicates that inorganic N and P are likely not in limited supply, and therefore, the enzyme activities at Loihi might be functioning to liberate organic C for microbial consumption. LAP hydrolyzes leucine from the N terminus of polypeptides and has been shown experimentally to be responsive to the addition of amino acids (55). However, there is no simple relationship between bulk measures of N availability and microbial N-acquiring LAP activity (6).…”
Section: Discussionmentioning
confidence: 99%
“…As soil P and moisture would influence the shifting of soil C in plant litter decomposition through increase N-P ratios in organisms or soil moisture by limiting the diffusion of substrates and enzymes, what's more, they will be also altered when N added [26,76]. N enrichment can also have negative effect on soil microbial growth by changing carbon, water or phosphorus [31,53].…”
Section: Soil Biologymentioning
confidence: 99%